The role of the book “Yrk Bitig” in the ancient Turkic written literature - Жумaбaевa А. А. (Journal of Oriental Studies, 2018)
There are many monuments of ancient Turkic writing written by the text of Sigdi, Middle Uighur, Manichaean, Syrian, Tibetan and Arabic script, and others. A huge area of distribution of monuments has been established: from Orkhon to the Danube, from Yakutia to the Gobi. Monuments of the ancient Turkic writing constitute an important link in the history of writing of the Turkic-speaking peoples. One of the unique and unique monuments of Turkic writing is “Yrk Bitig”. This article is devoted to the study of ancient Turkic written monuments, the author examines the areas of finding sites and reveals the history of the study of “Yrk bitig” (Book of divination)